ANALISA YANG MEMPENGARUHI PROFITABILITAS (Studi Pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indoinesia Tahun 2014-2018) - Mohklas, Mohklas; Latifah, Lina Khoiirul; Kurniawati, Endang (Jurnal Akuntansi dan Bisnis, 2023)
This study aims to examine the effect of cash turnover, accounts receivable turnover, inventory turnover, and working capital turnover on profitability. Population in this study are food and beverage companies listed on the IDX in 2014-2018. Sampling was carried out using a purposive sampling method with a total of 6 companies and a total sample of 30. Type of data used in this research is secondary data. Collection method is carried out through documentation studies and literature studies. Data analysis techniques using multiple linear regression analysis, and hypothesis testing (t-test). Results of this study indicate that cash turnover and accounts receivable turnover have no effect on profitability, while inventory turnover and working capital turnover have an effect on profitability. Keywords: Cash Turnover, Accounts Receivable Turnover, Inventory Turnover, Working Capital Turnover, and Profitability.